2021
DOI: 10.1364/prj.420326
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioned deconvolution method for high-resolution ghost imaging

Abstract: Ghost imaging (GI) can nonlocally image objects by exploiting the fluctuation characteristics of light fields, where the spatial resolution is determined by the normalized second-order correlation function g ( 2 ) . However, the spatial shift-invariant property of g ( 2 ) is distorted when the number of samples is limited, which hinders the deconvolution methods from improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Similar to the typical deconvolution operation [85,86] for traditional imaging that exploits the prior information of the system's transmission function, it is possible to achieve spatial super-resolution imaging in GI. By performing regularized preconditioning operations [87][88][89] on both the detection signal as well as the transmission matrix and solving the preconditioned problem via optimization algorithms, it is experimentally demonstrated that a high-quality imaging result with resolution beyond the diffraction limit can be obtained, and further theoretical analysis from the perspective of Fourier frequency domain also verifies its capability [90].…”
Section: Resolution Analysis In the High-dimensional Light-field Domainmentioning
confidence: 91%
“…Similar to the typical deconvolution operation [85,86] for traditional imaging that exploits the prior information of the system's transmission function, it is possible to achieve spatial super-resolution imaging in GI. By performing regularized preconditioning operations [87][88][89] on both the detection signal as well as the transmission matrix and solving the preconditioned problem via optimization algorithms, it is experimentally demonstrated that a high-quality imaging result with resolution beyond the diffraction limit can be obtained, and further theoretical analysis from the perspective of Fourier frequency domain also verifies its capability [90].…”
Section: Resolution Analysis In the High-dimensional Light-field Domainmentioning
confidence: 91%
“…Li et al used localization and thresholding to reduce the effect of the PSF in a correlation imaging system [32]. Preconditioned deconvolution methods [33] and the use of the coefficient of skewness [34] have been also suggested. Among the schemes based on image reconstruction, compressed sensing correlation imaging reduced the effect of the PSF on the imaging quality, using sparsity constraints to improve the spatial resolution of correlation imaging [24,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The narrowing of PSF by higher-order correlation of non-Rayleigh speckle fields has been reported [31] . Other schemes to enhance the resolution of GI have also been suggested, such as spatial low-pass filtering [18,20] , localizing and thresholding [32] , preconditioned deconvolution methods [33] , optical random speckle encoding based on hybrid wavelength and phase modulation scheme [34] , deep neural network constraints [35] , and speeded up robust features new sum of modified Laplacian (SURF-NSML) [36] .…”
Section: Introductionmentioning
confidence: 99%